From paratext to polysemiotic network: A holistic approach to the study of subtitled films - Silvester, Hannah (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2019)
This article proposes a framework for the study of interlingually subtitled films which draws on aspects of existing linguistic– and multimodal–analytical approaches. The methodology comprises contextual analysis at three levels. It proposes an initial study of the subtitling situation and technical aspects of the film. It then recommends an analysis of the plot, director interviews and reviews or articles written upon release of the film in order to identify key themes and the skopos of the film. Finally, in the light of information revealed in these stages of analysis, it proposes a close examination of the subtitles in context, in relation to the skopos of the film, and taking into account the film’s key themes and the cultural context(s) of its release. This allows for an analysis of subtitles which incorporates a variety of factors affecting the context of reception, integrating the multimodal nature of subtitling and the significance of cultural context and readability. Illustrative examples are taken from a case study of an English subtitled version of the French film, “La Squale”.